Literature Review: Terapi Nutrisi Pasien di Intensive Care Unit (ICU) - Devi Fila Delfia BR Simatupang; Ari Wahyuni; Liana Sidharti (Publikasi Indonesia, 2023)
Malnutrition is a common problem in most patients admitted to the hospital, especially in the intensive care unit, so it requires energy. The prevalence of malnutrition in intensive care units is 78.1% in developing countries and 50% in developed countries, while as many as 75% of intensive care unit patients experience malnutrition. Medical nutrition therapy is needed to provide proper and adequate nutrition so as to improve the patient's quality of life. Enteral nutrition therapy can be given within 48 hours of admission to the intensive care unit via a nasogastric tube or an alternative if contraindicated. Parenteral nutrition therapy can be started after 3-7 days if the patient cannot tolerate enteral nutrition. The nutritional needs of patients in the intensive care unit depend on the severity of the disease and previous nutritional status, so that proper and adequate nutrition can improve the patient's prognosis and quality of life.